Efficiency of Conducting Greenoperations When Growing Lemon in a Tranch Greenhouse - Bobosher Sheralievich Nortozhiev (Research Parks Publishing LLC, 2021)
The scientific article provides experimental material devoted to the study of the microclimate in a trench culture for growing lemon. Experiments have found that when growing lemon in a trench unheated greenhouse, the optimal temperature of 19.3-33.5 0C is observed during May-October months, the humidity of 62-85% remains in January-April, October-December, that is, during seven months without external influence of physical factors. In a trench culture, lemon in the annual development cycle undergoes four waves of shoot growth: the first wave of shoot growth in the crown occurs from the beginning to the end of May, the second - from the end of June to the second decade of July, the third - during August, and the fourth - from the first half of September to the end of October. In order to target the excess growth of shoots in the crown of trees and more efficient use of organic plastic substances by plants for laying generative buds in the first, second and third waves of growth, the pinching of green shoots must be carried out over the eighth leaf, and in the fourth wave of growth over the fourth leaf.